Transition between Different Renal Replacement Modalities: Gaps in Knowledge and Care—the Integrated Research Initiative. Issue 1 (January 2019) - Chan, Christopher; Combes, Gill; Davies, Simon; Finkelstein, Fred; Firanek, Catherine; Gomez, Rafael; Jager, Kitty J.; George, Vivek Jha; Johnson, David W.; Lambie, Mark; Madero, Magdalena; Masakane, Ikuto; et al.
Patients with end-stage kidney disease (ESKD) have different options to replace the function of their failing kidneys. The "integrated care" model considers treatment pathways rather than individual renal replacement therapy (RRT) techniques. In such a paradigm, the optimal strategy to plan and enact transitions between the different modalities is very relevant, but so far, only limited data on transitions have been published. Perspectives of patients, care-givers, and health professionals on the process of transitioning are even less well documented. Available literature suggests that poor coordination causes significant morbidity and mortality. This review briefly provides the background, development, and scope of the INTErnational Group Research Assessing Transition Effects in Dialysis (INTEGRATED) initiative. We summarize the literature on the transition between different RRT modalities. Further, we present an international research plan to quantify the epidemiology and to assess the qualitative aspects of transition between different modalities.